(untitled) (Bangladesh Journal of Medical Science, 2015)
Background: Road Traffic Accidents (RTA) are responsible for the greatest number of injuries and fatalities worldwide by killing around 1.2 million people each year and injuring another 50 million. Objective: To evaluate the present situation of Road Traffic Accidents (RTA) in Dhaka and to find out the pattern of injuries present in the bodies of drivers who were victims of fatal RTA. Materials & Method: This cross sectional descriptive study was conducted at the Dhaka Medical College (DMC) Morgue during the period January 2008 to December 2008. Specific findings regarding injury of drivers were noted during post mortem examinations. Results: A total of 2714 post mortems were conducted during the study period and out of which 813 were cases of RTA (29.95%). Maximum RTA occurred at daytime 282 (34.68%). Greater number of accidents occurred during September 90 (11.07%), followed by January 85 (10.45%). Maximum accidents took place on highways 650 (79.95%) and buses were the most dangerous vehicle causing highest number of causalities 307 (37.76%). Among the victims, 545 (67.03%) were male. Out of all victims 39 (4.80%) were drivers. Highest incidence of fatality in RTA (30.38%) was observed among the age group 21 to 30 years. Among the deceased drivers, 36 (92.30%) were literate. Considering injuries of the drivers 100% victims had multiple abrasions and bruises, lacerations were present in 35 (89.74%), and intracranial injury in 36 (90.31%) cases. Specific injuries of drivers like injury to lower limbs due to break pedal/clutch was found in 27 (69.23%) cases, steering wheel injury was present in 24 (61.53%) cases and whiplash injury was found in 15 (38.46%) cases. However, no seat belt injury was observed in any deceased driver. Conclusion: Strict enforcement of traffic law, using seat belts, maintaining fitness of vehicles, driving licenses, improving public awareness etc. can reduce this economical burden and protect vulnerable groups of people of our country. Bangladesh Journal of Medical Science Vol.14(4) 2015 p.346-351